Sports Education on Student Learning Motivation Seen from the Roles Involved in Sport Education Using Handball - Riki Ramadhan; Fauzan Effendy; Alrido Putra Pratama (Universitas Nahdlatul Ulama Cirebon, 2023)
Study purpose. This research aims to test the influence of Sport Education (SE) on students' learning motivation using handball, which can also be seen from the level of student motivation according to their role while participating in learning using SE Materials and methods. The participants involved were 58 students from one of the sports study programs in Indramayu. The research method used was an experiment with a one-shot case study design. The research instrument used the Learning Self-Regulation Questionnaire. Data analysis techniques were descriptive statistics and one sample t-test. Result. The research results stated that SE using handball influenced student learning motivation, with the roles of managers, referees, and match recorders in the excellent category and the roles of coaches, players and publications in the fair category. Conclusions. This research concludes that there was an influence of SE on students' learning motivation using handball. Further investigation is needed regarding the role of players who have the lowest motivation and also other affective domains besides motivation that cannot be revealed in this research. SE, as much as possible, is used as a strategy in teaching and made part of the curriculum in sports study programs because it is in line with the MBKM curriculum.